Faktor-Faktor Individu yang Berhubungan dengan Pelaksanaan Manajemen Terpadu Balita Sakit Di Sambas - Citra Trisna; Asfian Asfian (Jurnal Vokasi Kesehatan, 2017)
Abstract: Individual Factors Related To Implementation Of Integrated Management Of Childhood Illness (IMCI) In Sambas. Integrated Management of Childhood Illness (IMCI) is one of the government programs aimed at improving officer skills, strengthening health systems and improving care capabilities by families and communities. A public health centre is said to have implemented IMCI if it meets the criteria of carrying out IMCI at least 60% of the number of visits. Achievement of Implementation of IMCI at the public health centre in Sambas district in 2014 is still below 60%. Conducted research to determine the correlation between knowledge factor, performance and motivation toward the implementation of IMCI in public health centre Sambas District. This research was analytical descriptive with the cross-sectional design. The subjects of the study were the staff of the public health centre in Sambas district were 40 respondents. Data collection was done by using primary data through a checklist. Data were analyzed using univariate analysis with frequency distribution table and bivariate analysis using chi-square test. The result of bivariate analysis with chi-square test and significance of alpha 0,05 found no correlation between age (p-value = 0,905), knowledge (p-value = 0,064) and performance (p-value = 0,057) with IMCI implementation. Motivation factor (p-value = 0,013) had significant relation with IMCI implementation.Absrak: Faktor-Faktor Individu Yang Berhubungan Dengan Pelaksanaan Manajemen Terpadu Balita Sakit Di Sambas.Manajemen Terpadu Balita Sakit (MTBS) merupakan salah satu program pemerintah yang bertujuan untuk meningkatkan keterampilan petugas, memperkuat sistem kesehatan serta meningkatkan kemampuan perawatan oleh keluarga dan masyarakat. Puskesmas dikatakan sudah menerapkan MTBS apabila memenuhi kriteria melaksanakan MTBS minimal 60% dari jumlah kunjungan. Pencapaian Pelaksanaan MTBS pada puskesmas di wilayah Kecamatan Sambas tahun 2014 masih di bawah 60 %. Dilakukan penelitian untuk mengetahui hubungan faktor-faktor individu berupa pengetahuan, kinerja dan motivasi terhadap pelaksanaan MTBS di Puskesmas Wilayah Kecamatan Sambas. Penelitian ini bersifat deskriptif analitik dengan desain cross-sectional. Subjek penelitian adalah petugas Puskesmas wilayah kerja Puskesmas Sambas berjumlah 40 responden. Pengumpulan data dilakukan menggunakan data primer melalui cheklist. Data dianalisis menggunakan analisis univariat dengan tabel distribusi frekuensi dan analisis bivariat menggunakan uji chi-square. Hasil analisis bivariat dengan uji chi-square dan kemaknaan alpha 0,05 didapatkan tidak ada hubungan antara umur (p value = 0,905), pengetahuan (p value=0,064) dan kinerja (p value=0,057) dengan pelaksanaan MTBS. Faktor motivasi (p value= 0,013) mempunyai hubungan signifikan dengan pelaksanaan MTBS.